Rhubarb Enema Improved Colon Mucosal Barrier Injury in 5/6 Nephrectomy Rats May Associate With Gut Microbiota Modification - Ji, Chunlan; Deng, Yusheng; Yang, Aicheng; Lu, Zhaoyu; Chen, Yang; Liu, Xusheng; Han, Lijuan; Zou, Chuan (Frontiers in Pharmacology, 2020)
Rhubarb enema could effectively alleviate the progression of chronic kidney disease (CKD), however, the specific mechanism remains unclear. We previously reported a reduction of uremic toxins, oxidative stress and inflammation after rhubarb intervention which may related to gut microbiota modification. However, whether rhubarb protects the intestinal barrier by regulating gut microbiota related to the intestinal barrier in CKD remains unclear. Here we further investigated the effects of rhubarb enema on gut microbiota, intestinal barrier and renal function in 5/6 nephrectomy animal model. Our results indicated that rhubarb enema regulated gut microbiota dysbiosis, improved the intestinal barrier, suppressed systemic inflammation and alleviated the progression of CKD. More specifically, rhubarb treatment inhibited overgrowth of conditional pathogenic gut bacteria, including Akkermansia, Methanosphaera, and Clostridiaceae with CKD. The modification of gut microbiota with rhubarb intervention displayed significant correlation to markers of intestinal barrier, TLR4–MyD88–NF-B inflammatory response, and renal function. These results demonstrated that the anti-inflammatory and therapeutic effects of rhubarb enema on kidney injury might primary mediated by restore of intestinal barrier and involve several functional enteric bacteria.